Dinamika Proses Perumusan Kebijakan Perubahan Status Desa menjadi Kelurahan (Studi Kasus di Desa Pakkat Hauagong Kecamatan Pakkat Kabupaten Humbang Hsundutan) - Simamora, Hanaya C (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2012)
This study examines the dynamics of the policy process in which changes the "desa" into "kelurahan". The Consequence of the government village honorably discharged from office and position. Thus, the change is not infrequently receive rejection and defiance of them. Hauagong Pakkat Village, in Subdistrict Pakkat Humbang Hasundutan, selected as locus because the village is willing to accept and initiate change. This study examines some of the issue related to the process of policy formulation "desa" to "kelurahan" status changes, particularly regarding the importance of the village government and the regional development banks, the dynamics of the policy formulation process and considerations that drive and inhibit that they are willing to accept the policy.